Circulating cell-free endometrial DNA level is unaltered during menstruation and in endometriosis. Issue 11 (27th September 2022) - Yuwono, N L; Alonso, A; Abbott, J; Houshdaran, S; Henry, C E; Rodgers, R; Ford, C E; Warton, K
Abstract: STUDY QUESTION: Is circulating cell-free DNA (cirDNA) from the endometrium elevated during menstruation and in endometriosis? SUMMARY ANSWER: Endometrial cirDNA does not increase during menstruation and is not elevated in endometriosis. WHAT IS KNOWN ALREADY: Changes in cirDNA associated with common benign conditions are a potential source of false positives in cancer diagnostic applications, but also present an opportunity for biomarker development for diseases such as endometriosis. Elevated cirDNA has been reported in endometriosis patients compared to healthy community controls, but no difference in total or endometrial cirDNA has been found between patients with endometriosis and patients with other gynaecological conditions. Likewise, menstruation is a potential driver of changes in cirDNA levels and tissue profile, but total and endothelial cirDNA do not increase during menstruation. STUDY DESIGN, SIZE, DURATION: For endometriosis comparisons, 59 participants with surgically confirmed endometriosis and 27 laparoscopic patients without endometriosis (hospital controls) were prospectively recruited, while 25 healthy community participants (healthy controls) were recruited in a university setting. Total and endometrial cirDNA and cirDNA fragmentation were measured across the three groups. For menstrual comparisons, 36 matched non-menstruating and menstruating samples were collected from healthy women recruited within a university setting, and the endometrial cirDNA was compared between the two groups. PARTICIPANTS/MATERIALS, SETTING, METHODS: cirDNA was extracted from venous blood plasma then quantitated by quantitative PCR of ALU repetitive element (115 bp) and TP53 gene sequence (105 bp) for total concentration. cirDNA derived from the endometrium was quantitated by methylation-specific droplet digital PCR of a FAM101A region (69 bp) after bisulfite conversion of the DNA. A cirDNA size fragmentation ratio was obtained by quantifying a long segment of ALU repetitive element (247 bp) and expressing the amount relative to the 115 bp ALU target. MAIN RESULTS AND THE ROLE OF CHANCE: No differences in cirDNA level were found in any comparison populations in this study. Mean total cirDNA was unchanged between healthy controls ( ALU -115–3.31 ng/ml; TP53– 2.73 ng/ml), hospital controls ( ALU -115–3.47 ng/ml; TP53– 2.83 ng/ml) and endometriosis patients ( ALU -115–3.35 ng/ml; TP53– 2.66 ng/ml). Likewise, endometrial cirDNA was unchanged between healthy controls (18.3 copies/ml), hospital controls (20.6 copies/ml) and endometriosis patients (22 copies/ml). Endometrial cirDNA did not change during menstruation (non-menstruating: 38 copies/ml; menstruating: 33 copies/ml). Irrespective of endometriosis diagnosis, blood from patients undergoing laparoscopy (hospital controls: 0.77; endometriosis patients: 0.79), had a significantly higher cirDNA size ratio than community-recruited healthy controls (0.64), indicating increased abundance of long cirDNA fragments. LIMITATIONS, REASONS FOR CAUTION: It was not possible to completely match the age, BMI and parity between the three cohorts investigated, however of these, only age has been shown to influence circulating DNA levels and not within the age range of our cohort. Blood from community-recruited healthy women and women undergoing laparoscopy was collected via antecubital vein venepuncture (processed within 3 h) and with either peripheral cannula or venepuncture (processed within 6 h), respectively, which could potentially impact the size distribution of circulating DNA fragments. For the collection of non-menstruating phase blood samples, we did not differentiate between follicular phase, ovulation and luteal phase. Thus, only the mensturating samples were collected at a consistent phase, and any fluctuations in cirDNA that occur at the other phases may have obscured small changes during menstruation. WIDER IMPLICATIONS OF THE FINDINGS: There is no evidence that cirDNA has potential as a diagnostic biomarker for endometriosis. Endometriosis, representing a common benign gynaecological condition, and menstruation, representing a normal physiological occurrence in women, should not affect methylation-based diagnostics in other disease areas, including oncology. STUDY FUNDING/COMPETING INTEREST(S): N.L.Y.: Australian Government Research Training Program (RTP) Stipend through The University of New South Wales, Translational Cancer Research Network PhD Scholarship Top-Up Award via the Cancer Institute NSW, Beth Yarrow Memorial Award in Medical Science, UNSW Completion Scholarship; C.E.H.: Gynaecological Oncology Fund of the Royal Hospital for Women; K.W.: Ovarian Cancer Research Foundation and CAMILLA AND MARC. C.E.F.: UNSW Women's Wellbeing Academy and the Australian Human Rights Institute. We declare the following competing interest: K.W. holds stock in Guardant Health, Exact Sciences and Epigenomics AG. No other authors have competing interests. TRIAL REGISTRATION NUMBER: N/A.